Implementasi Algoritma A dalam Sistem Informasi Geografis Pemetaan Rute Rumah Sakit Berbasis Web Menggunakan Leaflet - Adyatma Yoransa, Vito; Witriyono, Harry (Institut Teknologi Garut, 2025)
Finding the fastest route to health care facilities is one of the most important needs in emergency situations. This study aims to develop a web-based Geographic Information System (GIS) that can determine the fastest route to the nearest hospital in Bengkulu Province. This system uses the A* algorithm to calculate the shortest route and Leaflet.js to display an interactive map based on OpenStreetMap. The system development method used is the Rational Unified Process (RUP), which consists of four phases, namely inception, elaboration, construction, and transition. The results of the study show that the system is capable of displaying hospital locations, providing a visualization of the shortest route map, and displaying interactive route navigation instructions. Testing using five black-box test scenarios shows that all key features work as expected. The contribution of this study is to provide an interactive WebGIS solution for medical route search with high efficiency that has not been widely implemented in local navigation systems.